STRATEGI PEMERINTAH KOTA AMBON DALAM MEWUJUDKAN KOTA LAYAK ANAK - Sidiq Fandiyanan Patty; Mike J. Rolobessy (LPPM Institut Pendidikan Nusantara Global, 2023)
The results of the study show that Ambon City has received the title of a Primary Child-friendly City in Makassar in 2019 and also has a legal basis which is the Regional Regulation Number 1 of 2019 concerning Child-friendly Cities. Based on this, one of the ways to create a child-friendly city according to Kooten's theory in Salusu (1996: 104) are through 4 strategies, namely: a) Organizational strategy, b) Program strategy, c) Supporting resource strategy, and d) Institutional strategy. The methodology used in this study is qualitative with primary and secondary data. Data collection techniques used are interview, observation, and documentation techniques. The results reveal that even though Ambon City has had the label of Primary Child-friendly City, the Disability-friendly public facilities are still not adequate yet. Besides, there is no child-friendly integrated public spaces that exist in Ambon City.